Coaggregation of Candida dubliniensis with Fusobacterium nucleatum - Jabra-Rizk, Mary Ann (American Society for Microbiology, 1999)
The binding of microorganisms to each other and oral surfaces contributes to the progression of microbial infections in the oral cavity. Candida dubliniensis, a newly characterized species, has been identified in human immunodeficiency virus-seropositive patients and other immunocompromised individuals. C. dubliniensis phenotypically resembles Candida albicans in many respects yet can be identified and differentiated as a unique Candida species by phenotypic and genetic profiles. The purpose of this study was to determine oral coaggregation (CoAg) partners of C. dubliniensis and to compare these findings with CoAg of C. albicans under the same environmental conditions. Fifteen isolates of C. dubliniensis and 40 isolates of C. albicans were tested for their ability to coaggregate with strains of Fusobacterium nucleatum, Peptostreptococcus micros, Peptostreptococcus magnus, Peptostreptococcus anaerobius, Porphyromonas gingivalis, and Prevotella intermedia. When C. dubliniensis and C. albicans strains were grown at 37°C on Sabouraud dextrose agar, only C. dubliniensis strains coaggregated with F. nucleatum ATCC 49256 and no C. albicans strains showed CoAg. However, when the C. dubliniensis and C. albicans strains were grown at 25 or 45°C, both C. dubliniensis and C. albicans strains demonstrated CoAg with F. nucleatum. Heating the C. albicans strains (grown at 37°C) at 85°C for 30 min or treating them with dithiothreitol allowed the C. albicans strains grown at 37°C to coaggregate with F. nucleatum. CoAg at all growth temperatures was inhibited by mannose and α-methyl mannoside but not by EDTA or arginine. The CoAg reaction between F. nucleatum and the Candida species involved a heat-labile component on F. nucleatum and a mannan-containing heat-stable receptor on the Candida species. The CoAg reactions between F. nucleatum and the Candida species may be important in the colonization of the yeast in the oral cavity, and the CoAg of C. dubliniensis by F. nucleatum when grown at 37°C provides a rapid, specific, and inexpensive means to differentiate C. dubliniensis from C. albicans isolates in the clinical laboratory.